Inclusive Practices: Strengthening Character Through Social Participation of Deaf Students: Praktek Inklusif : Penguatan Karakter Melalui Partipasi Sosial Mahasiswa Tunarungu - Amka, Amka; Mirnawati, Mirnawati (Universitas Muhammadiyah Sidoarjo, 2020)
This study aims to observe and analyze the practice of social participation of tunarunggu students in realizing character strengthening on the inclusive campus of Lambung Mangkurat University, Banjarmasin. Research respondents were 31 people in one class, consisting of 5 deaf students and 26 other peer students. Social participation is examined through three key elements, namely: social relations of friendship, acceptance of classmates, and student perceptions. The study uses a quantitative approach with survey methods. Data collection techniques using interviews, questionnaires, and documentation. Data analysis techniques using descriptive statistics. The results of the study show the success of strengthening character education through social participation in inclusive settings for students who are disabled with their peers or vice versa